Comparison of Cycle Outcomes among Women with Endometrioma or Non-Functional Cysts Versus Control - Ozkaya, Enis; Cogendez, Ebru; Tozkir, Elif; Unsal, Saadet; Yavuz, Ahmet; Tunali, Gulden; Uzun, Ozgur; Ergen, Evrim Bostancı; Eser, Semra Kayatas (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: This study aimed to compare cycle outcomes among women with endometrioma or non-functional cysts versus control. STUDY DESIGN: Women under 35 years of age with unexplained infertility underwent in vitro fertilization cycle. Two hundred and ninety-nine women were included in this study. Study groups consist of women with endometrioma (n=82) or non-functional ovarian cysts (n=100) and control group (n=117). Women in each group were selected consecutively. Groups were matched for age and ovarian reserve and compared in terms of in vitro fertilization cycle outcome. RESULTS: There were no significant differences among groups in terms of mean age, early follicular phase Follicle-Stimulating Hormone, and anti-müllerian hormone levels (p>0.05). Baseline total antral follicle counts were similar among groups (p>0.05). There were significant differences among groups in terms of mean starting and total gonadotropin dose, peak estradiol level, total oocyte number, and mature oocyte numbers (p<0.05). Clinical pregnancy rates were 10.7%, 17.3%, and 31.6% in groups with non-functional cyst, endometrioma and control group respectively (p<0.05). The presence of a non-functional cystic mass of ovary on the starting day of stimulation was a risk factor for poor cycle outcome in terms of clinical pregnancy rates [OR=0.5 (95 % CI; 0.2-0.9, p=0.03)]. CONCLUSION: Our data showed that the presence of any kind of cystic mass of the ovary especially the non-functional cysts on the starting day of stimulation was a risk factor for poor cycle outcomes in terms of clinical pregnancy rates.